Reflections on the Actions of Civil Society in Building the PNE 2014/2024 - Idevaldo da Silva Bodião (Universidade Federal do Rio Grande do Sul, 2016)
Based on concepts such as democracy and social participation, this essay discusses the civil society incidence into building the National Education Plan 2014/2024, from the work of the Brazilian Campaign for the Right to Education. For this purpose, some aspects of the CONAE/2010 are described, some elements from the official text in process in the National Congress are presented and the actions of the Campaign along each of these steps are reported. At the end, the limits for civil society intervention, the weak mechanisms for its participation and the disproportion between the mobilized effort and the changes that actually take effect, elements that may discourage future participation of civil society, are highlighted.